2004
DOI: 10.1182/blood-2003-12-4443
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy and safety of platelets treated with a photochemical process for pathogen inactivation: the SPRINT Trial

Abstract: We report a transfusion trial of platelets photochemically treated for pathogen inactivation using the synthetic psoralen amotosalen HCl. Patients with thrombocytopenia were randomly assigned to receive either photochemically treated (PCT) or conventional (control) platelets for up to 28 days. The primary end point was the proportion of patients with World Health Organization (WHO) grade 2 bleeding during the period of platelet support. A total of 645 patients (318 PCT and 327 control) were evaluated. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
580
6
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(617 citation statements)
references
References 35 publications
25
580
6
6
Order By: Relevance
“…However, inactivation to below the limit of detection in the assay was observed in half of the replicates following 3.0 J/cm 2 UVA treatment and fewer than 1.3 log 10 TCID 50 /mL was detected in the remaining replicates. Overall, inactivation of 7.6 ± 1.4 log TCID 50 of CHIKV in plasma was observed (Table 2). Given the 200:1 ratio between the TCID 50 and gEq/mL, levels of inactivation of 8.7 and 9.9 log gEq can be calculated for platelets and plasma, respectively, indicating a level of protection comparable to the highest levels of viremia observed in infected blood samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inactivation to below the limit of detection in the assay was observed in half of the replicates following 3.0 J/cm 2 UVA treatment and fewer than 1.3 log 10 TCID 50 /mL was detected in the remaining replicates. Overall, inactivation of 7.6 ± 1.4 log TCID 50 of CHIKV in plasma was observed (Table 2). Given the 200:1 ratio between the TCID 50 and gEq/mL, levels of inactivation of 8.7 and 9.9 log gEq can be calculated for platelets and plasma, respectively, indicating a level of protection comparable to the highest levels of viremia observed in infected blood samples.…”
Section: Resultsmentioning
confidence: 99%
“…47 In vitro studies have shown that photochemical treatment with amotosalen and UVA does not substantially affect platelet or plasma function 40,41,48,49 and clinical trials indicated that transfusion of psoralen-treated platelets or plasma to patients does not result in adverse immunologic or hemorrhagic responses. [50][51][52][53] More than a million kits to prepare IBS platelets and plasma have been sold since the introduction of the system in Europe. Detailed haemovigilance and post marketing surveillance in Europe since 2003 continues to demonstrate safety and efficacy of the treated products.…”
Section: Introductionmentioning
confidence: 99%
“…We also agree that some studies did not report an increased usage of platelet components with Amotosalen/UVA, but others did in fact observe a decreased count increment (CI) and corrected count increment (CCI), [12][13][14] which could be explained primarily by an increased platelet clearance. Finally, we would like to emphasize again (as we state at the end of our paper) that the primary goal of our study was to better understand the effect of Amotosalen/UVA on platelet function at the molecular level in order to develop newer and better pathogen inactivation technologies.…”
mentioning
confidence: 67%
“…Treatment often includes prednisone, infusions of intravenous immunoglobulin, and platelet transfusion [7]. Platelet transfusion, however, can lead to antibody responses in recipients, and as a result, there has been considerable research directed at the development of pathogeninactivated platelet products to reduce the risks of these reactions [8][9][10][11][12][13]. This article is concerned with methodological challenges arising in the design and analysis of randomized trials directed at comparing the effectiveness of standard and pathogen inactivated platelets.…”
Section: Platelet Transfusion Trials In Thrombocytopeniamentioning
confidence: 99%
“…The timing and need for transfusions vary considerably between patients because of differences in the severity of the underlying condition, the schedule and intensity of chemotherapy, and other known and unknown factors. Protocols often dictate that data on the responses to a pre-specified number of transfusions are to be analysed [9]. If all patients are followed until they experience the pre-specified number of transfusions, then this is a reasonable strategy.…”
Section: Platelet Transfusion Trials In Thrombocytopeniamentioning
confidence: 99%